English proficiency of Japanese third-age learners: A Quantitative Inquiry - San Jose, Dominic Bryan; Guitche, Melona; Bual, Joel; Madrigal, Dennis (Technium Social Sciences Journal, 2024)
The EFL (English as a Foreign Language) participation and engagement of third-age learners, whose ages range from 50 up to 70 and above has received global attention. Japanese third-age learners’ pursuit of English competence exhibits broader societal trends and personal desires for lifelong learning. Utilizing a descriptive-correlational approach, the study assessed the level of English language proficiency (ELP) of 59 Japanese third-age learners registered in the 2023-2024 EFL program in five cities of Aichi prefecture, Japan, when they were taken as a whole and when they were demographically grouped by sex, age, educational background, and weekly average study time. The results show that on average, third-age learners in Japan achieve an intermediate level of English proficiency or B1, with variances observed attributed to demographic criteria such as sex, age, educational background, and weekly English study time. The study found a significant relationship between ELP and the respondents’ demographic, indicating that ELP levels are influenced by sex, age, educational attainment, and the number of hours spent learning English per week, with males showing higher proficiency and older learners generally showing higher levels. The study underscores the need for tailored English language instruction for third-age learners, taking into account their specific demographics. It also considers the policy implications of institutionalizing programs for third-age learners in Japan, aiming to promote active aging, social integration, and overall well-being. Researchers, teachers, and curriculum designers may use this study as one of the bases for developing tailored curricula and instructional materials for third-age learners.